2017
DOI: 10.1097/ajp.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

Cold Pain Threshold Identifies a Subgroup of Individuals With Knee Osteoarthritis That Present With Multimodality Hyperalgesia and Elevated Pain Levels

Abstract: Objectives: Cold hyperalgesia has been established as an important marker of pain severity in a number of conditions. This study aimed to establish the extent to which patients with knee osteoarthritis (OA) demonstrate widespread cold, heat, and pressure hyperalgesia. OA participants with widespread cold hyperalgesia were compared with the remaining OA cohort to determine whether they could be distinguished in terms of hyperalgesia, pain report, pain quality, and physical function.Methods: A total of 80 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…The result is consistent with daCosta DiBonaventura et al [40] reported that adults with OA report worse quality of life, greater number of hospitalizations and reduced productivity than those without also, Wright et al [46], demonstrated widespread cold, heat, and pressure hyperalgesia. OA participants with widespread cold hyperalgesia were compared with the remaining OA cohort to determine whether they could be distinguished in terms of hyperalgesia, pain report, pain quality, and physical function who attended the laboratory at Royal Perth Hospital in Australia mentioned that participants with knee OA exhibited reduced scores on the physical health subscale of the SF-36 (P= 0.01) Recent study done [47] evaluated health-related quality of life (HRQoL) in primary knee osteoarthritis (KOA) patients using the osteoarthritis knee hip quality of life (OAKHQoL) questionnaire recruited from the Rheumatology and Rehabilitation outpatient clinic, Cairo University concluded that Egyptian patients with primary KOA have relatively poor HRQoL.…”
Section: Discussionsupporting
confidence: 81%
“…The result is consistent with daCosta DiBonaventura et al [40] reported that adults with OA report worse quality of life, greater number of hospitalizations and reduced productivity than those without also, Wright et al [46], demonstrated widespread cold, heat, and pressure hyperalgesia. OA participants with widespread cold hyperalgesia were compared with the remaining OA cohort to determine whether they could be distinguished in terms of hyperalgesia, pain report, pain quality, and physical function who attended the laboratory at Royal Perth Hospital in Australia mentioned that participants with knee OA exhibited reduced scores on the physical health subscale of the SF-36 (P= 0.01) Recent study done [47] evaluated health-related quality of life (HRQoL) in primary knee osteoarthritis (KOA) patients using the osteoarthritis knee hip quality of life (OAKHQoL) questionnaire recruited from the Rheumatology and Rehabilitation outpatient clinic, Cairo University concluded that Egyptian patients with primary KOA have relatively poor HRQoL.…”
Section: Discussionsupporting
confidence: 81%
“…In a recent publication we have demonstrated that a subgroup of patients with increased CPTs also present with widespread multimodality hyperalgesia and increased PainDETECT scores. 27 …”
Section: Discussionmentioning
confidence: 99%
“…5). A previous study has examined baseline data for this cohort 5 , finding that the 43.8% of participants who exhibited widespread cold hyperalgesia (CPT > 12.25 C, based on Zscores from a matched healthy group) also showed widespread mechanical and heat hyperalgesia, higher painDETECT scores, greater pain and disability, and lower quality of life scores. There were no significant differences between Placebo and Active groups for these measures of pain and sensitization, or for age, gender or BMI (Supplementary Data Table (A)).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Physical assessment of locomotion provides an objective measure of impact on function 16 . In cross-sectional studies, quantitative sensory testing (QST) has demonstrated the presence of widespread multi-modality hyperalgesia 17e19 which may be an indicator of centrally-driven pain 4,5,20 . Measuring change in hyperalgesia at local and distant test sites following a pharmaceutical intervention therefore enables evaluation of its impact on the nociceptive system.…”
Section: Introductionmentioning
confidence: 99%